CLINIC AND TREATMENT OF DIPLOCOCCOSIS IN LAMBS - Kuçkarova S.K; Allamurodova M.M (TADQIQOTLAR.UZ, 2024)
This scientific article describes cases of mixed diplococcosis and pasteurellosis infections in lambs, the dynamics of their spread, disease diagnostics, clinical signs, as well as methods of prevention and treatment.